2016
DOI: 10.1093/jrr/rrw025
|View full text |Cite
|
Sign up to set email alerts
|

Radiological properties of nanocomposite Fricke gel dosimeters for heavy ion beams

Abstract: The radiological properties of nanocomposite Fricke gel (NC-FG) dosimeters prepared with different concentrations of nano-clay, perchloric acid and ferrous ions in deaerated conditions were investigated under carbon and argon ion beam irradiation covering a linear-energy-transfer (LET) range of 10 to 3000 eV/nm. We found that NC-FG exhibits radiological properties distinct from those of conventional Fricke gel. The radiation sensitivity of NC-FG is independent of the LET and is nearly constant even at very hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 37 publications
1
25
1
Order By: Relevance
“…Depth vs dose distribution across our T-175 flask was visually represented utilizing a Fricke gel dosimeter, as previous studies have reported ferrous xylenol gels can be used as dosimeters and can therefore provide a quality method for detecting dose distribution 20,21 . Irradiation oxidizes Fe 2+ to Fe 3+ which changes the color of the originally yellow gel to various orange-color combinations depending on the dosage at that specific depth.…”
Section: Resultsmentioning
confidence: 99%
“…Depth vs dose distribution across our T-175 flask was visually represented utilizing a Fricke gel dosimeter, as previous studies have reported ferrous xylenol gels can be used as dosimeters and can therefore provide a quality method for detecting dose distribution 20,21 . Irradiation oxidizes Fe 2+ to Fe 3+ which changes the color of the originally yellow gel to various orange-color combinations depending on the dosage at that specific depth.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that HD-V2 Gafchromic™ films have a different structure from the other Gafchromic™ films as they feature a 12 µm thin active layer on a 97 µm polyester substrate. The LET dependence is common to other types of dosimeters; however, recently developed nanocomposite Fricke gel dosimeters have shown to have no dependence on the LET in a wide LET range [116,117].…”
Section: Radiochromic Films Response To Relevant Physical Quantitiesmentioning
confidence: 99%
“…PGD was also tested with heavy ion beams[40]. Recently, Maeyama et al used the nano-composite Fricke gel (NC-FG), a type of FGD, with carbon and argon ion beams, whose LET ranged from 10 to 3000 eV/μm[41]. NC-FG showed a consistent dose response for the range of LET tested in their study.…”
Section: Clinical Applicationsmentioning
confidence: 99%